1986
DOI: 10.1007/bf00237479
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of isometric force in the ?motor? thalamus

Abstract: The relationship between single cell activity in the "motor" thalamus and the generation of isometric force between the fingers has been investigated in 2 monkeys. Neurons related to the task were found in the thalamic motor regions VLo, VPLo, and VA where microstimulation occasionally elicited motor reactions in hand and fingers. 58% of these 55 neurons, designated "typical", showed modulation of their discharge patterns with force similar to neurons in precentral cortex and could be assigned to one of 5 disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…If VL neurones do project to multiple cortical representations of the same muscle, then the cortical extent of influence (in terms of number of joints) of individual cerebellar nuclear neurones would be determined solely by the degree of divergence in the cerebellothalamic pathway. This notion is consistent with previous findings that single-joint movements are typically evoked by microstimulation of the motor thalamus (Asanuma and Hunsperger, 1975;Strick, 1976b;Anner-Baratti et al, 1986;Buford et al, 1996;Vitek et al, 1996), whereas multijoint movements are a feature of cerebellar nuclear microstimulation (Schultz et al, 1976(Schultz et al, , 1979Rispal-Padel et al, 1981;Cicirata et al, 1989;Ekerot et al, 1995). It must be stressed, however, that the cerebellothalamocortical pathway was ruled out as the mediator of these cerebellar stimulation effects in most of these studies (Schultz et al, 1976(Schultz et al, , 1979Cicirata et al, 1989;Ekerot et al, 1995).…”
Section: Divergence In the Motor Thalamocortical Projectionsupporting
confidence: 82%
See 1 more Smart Citation
“…If VL neurones do project to multiple cortical representations of the same muscle, then the cortical extent of influence (in terms of number of joints) of individual cerebellar nuclear neurones would be determined solely by the degree of divergence in the cerebellothalamic pathway. This notion is consistent with previous findings that single-joint movements are typically evoked by microstimulation of the motor thalamus (Asanuma and Hunsperger, 1975;Strick, 1976b;Anner-Baratti et al, 1986;Buford et al, 1996;Vitek et al, 1996), whereas multijoint movements are a feature of cerebellar nuclear microstimulation (Schultz et al, 1976(Schultz et al, , 1979Rispal-Padel et al, 1981;Cicirata et al, 1989;Ekerot et al, 1995). It must be stressed, however, that the cerebellothalamocortical pathway was ruled out as the mediator of these cerebellar stimulation effects in most of these studies (Schultz et al, 1976(Schultz et al, , 1979Cicirata et al, 1989;Ekerot et al, 1995).…”
Section: Divergence In the Motor Thalamocortical Projectionsupporting
confidence: 82%
“…It is equally possible, however, that the multiple and widespread motor thalamocortical projection reflects the multiple and widespread representation of individual muscles in the motor cortex (Kwan et al, 1978;Pappas and Strick, 1981a,b;Tanji and Wise, 1981;Donoghue and Wise, 1982;Drew, 1984, 1985;Huang et al, 1988). Indeed, electrical microstimulation of the motor thalamus has been shown to evoke movements predominantly restricted to a single joint in awake monkeys (Strick, 1976b;Anner-Baratti et al, 1986;Buford et al, 1996;Vitek et al, 1996) and cats (Asanuma and Hunsperger, 1975). The functional extent of influence of single motor thalamocortical neurones will be an important area of study for the future, particularly with respect to current ideas concerning the development of topography in the motor system raised in the introduction.…”
Section: Divergence In the Motor Thalamocortical Projectionmentioning
confidence: 97%
“…Using single cell recording in macaque monkeys (Ashe 1997), the correlation between firing rates of cortical neurones and force of both isometric and dynamic grip tasks has been demonstrated to be mainly monotonic or linear. Linear relationships have been observed primarily in primary motor cortex (Evarts, 1968; Smith et al , 1975; Hepp-Reymond et al , 1978; Evarts et al , 1983; Wannier et al , 1991; Georgopoulos et al , 1992), and also for neurones in somatosensory cortex (Wannier et al , 1991), premotor cortex (Hepp-Reymond et al , 1994), supplementary motor area (Smith et al , 1975) and thalamus (Anner-Baratti et al , 1986). Functional imaging techniques allow the activity in larger populations of neurones to be studied simultaneously across all brain regions, which allows inference about activity relationships between one population of neurones and another.…”
Section: Discussionmentioning
confidence: 99%
“…We found that microstimulation induced more frequent motor responses in the rostral than in the caudal motor thalamus. Similar results were previously reported (Strick, 1976; Anner‐Baratti et al ., 1986; Vitek et al ., 1994; Buford et al ., 1996; Miall et al ., 1998) although there is no consensus about the percentage and threshold of response to microstimulation in the motor thalamus. One striking result of the present study is that bicuculline injections induced a dramatic increase in the excitability of thalamic neurons.…”
Section: Discussionmentioning
confidence: 99%